Assédio moral no trabalho acadêmico e as vivências de prazer e sofrimento na concepção da psicodinâmica do trabalho em uma instituição pública em São Luís - MA - Demetrio, Jaqueline Alves da Silva (2019)
This study investigates bullying in academic work and the experiences of pleasure and suffering in the conception of psychodynamics at work in a public institution in São Luis - MA. Specifically, it aims to verify the relationships between the academic administrative process of work, the conditions under which it develops and the possible physical and mental illness of these subjects through the characterization of the work context in the organizational dimension, conditions and socio-professional relations, as well as how to describe the experiences of suffering and pleasure, which is used as a strategic way of survival or mediation to relieve or neutralize suffering. The theoretical and methodological support is supported by work psychodynamics, labor clinic and multidisciplinary studies of norms and current scientific research on the problem investigated. Four clinical meetings were held with twelve participants, administrative staff, whose reports after transcription by report were subjected to validation, resulting in the presentation of a reality that, while recognizing the difficulties that the public university is experiencing, has a small negative impact on the work, indicating specific aspects of bullying at work, where the suffering experiences do not stand out before the pleasure experiences that the subjects find in their peers and in others that are part of the participants' socio-professional coexistence. Regarding survival strategies, they are marked by experiences of pleasure with coworkers and the academic community that rescue the feeling of dignity and professional appreciation.